Stationary battery technologies in the U.S.: Development Trends and prospects. (August 2017) - Telaretti, E.; Dusonchet, L.
Abstract: In the last years, stationary battery systems started to attract the attention of stakeholders thanks to their unique ability to decouple power generation and load over time, providing the ancillary services necessary for the stability and the reliability of the electrical system. This is especially true in the presence of high levels of penetration of renewable energy technologies, like wind and solar photovoltaic (PV), because of increased fluctuations in the electricity produced by these renewable sources. Despite the growing interest in energy storage technologies, the academic literature has not completely assessed the development trends of this sector. In order to fill this gap, this study strives to address the trends in the spread of stationary battery systems within the U.S. territory. First, the U.S. policy legislation within the different U.S. states is reviewed, with particular emphasis on support policies put in place in the different states. Second, based on the analysis of the Department of Energy (DOE) Energy Storage Database, the main trends in battery systems installations within the U.S. are identified and presented in this paper, with reference both to the viable use cases and to the main electrochemical technologies currently spread in the storage market. The analysis carried out in this work could help stakeholders to assess the impact of energy storage policies in the different U.S. states, identifying the future trends and the most promising markets within the U.S. territory.